2023
DOI: 10.1039/d2nr06821d
|View full text |Cite
|
Sign up to set email alerts
|

Cationic vacancy engineering of p-TiO2 for enhanced photocatalytic nitrogen fixation

Abstract: Defect engineering is one of the effective strategies to regulate and control catalyst properties. Constructing appropriate catalytic active centers effectively tunes the electronic andsurface properties of the catalyst to achieve...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 57 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…7b shows the removal of total organic carbon (TOC) in the reaction, which demonstrates the production of by-products in the reaction. The reactive oxygen species (ROS) of V Mn,O were determined by EPR 44 (Fig. 7c), and the 3, 4 and 7 characteristic peaks correspond to the singlet oxygen ( 1 O 2 ), hydroxyl radical (OH·), and superoxide anion (O 2 ˙ − ), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7b shows the removal of total organic carbon (TOC) in the reaction, which demonstrates the production of by-products in the reaction. The reactive oxygen species (ROS) of V Mn,O were determined by EPR 44 (Fig. 7c), and the 3, 4 and 7 characteristic peaks correspond to the singlet oxygen ( 1 O 2 ), hydroxyl radical (OH·), and superoxide anion (O 2 ˙ − ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al 11 constructed Bi 2 WO 6 hollow microspheres with oxygen vacancies and found that their high catalytic effect originated from the fast charge transfer hindering carrier complexation. Ding et al 12 constructed Ti vacancy-rich p -TiO 2 and found that its high photocatalytic efficiency was due to the stronger carrier separation and transport.…”
Section: Introductionmentioning
confidence: 99%
“…5 Therefore, XPS can serve as a robust technique for the identification of cationic vacancies or unsaturated sites within defective materials in comparison to defect-free materials. The presence of Ti vacancy defects was probed via XPS by Ding et al 52 As shown in Fig. 6e and f, the XPS peaks of p-TiO 2 exhibit a shift towards higher binding energy compared to those of n-TiO 2 .…”
Section: Characterization Of Cation Vacanciesmentioning
confidence: 99%
“…The concentration of vacancies exhibited a gradual decrease as the treatment temperature increased, potentially attributed to atomic rearrangement. Ding et al 52 employed EPR to investigate Ti cation vacancies in TiO 2 (Fig. 6h).…”
Section: Characterization Of Cation Vacanciesmentioning
confidence: 99%
See 1 more Smart Citation